Schizotypal Traits in Children with Autism Spectrum Disorder and the Impact on Social, Emotional and Behavioral Functioning - Evdokia Tagkouli; Evangelia Chrysanthi Kouklari; Bruce J. Tonge; Vassiliki Ntre; Artemios Pehlivanidis; Nikos C. Stefanis; Christos Pantelis; Katerina Papanikolaou (Brain Sciences)
Background: Schizotypal traits are considered to be clinical and cognitive features of Schizotypal Disorder in children (SDc). These traits are also seen in children and adolescents with high-functioning Autism Spectrum Disorder (ASD). This study examines the influence of schizotypal traits (and their severity) on the capacity of children with ASD to manage emotions, develop relationships with others, and adapt in school and family life. Methods: The Schizotypal traits of 63 children (6–12 years old) with High Functioning ASD were measured by the Melbourne Assessment of Schizotypy in Kids (MASK). Parents and teachers of the participating children completed the Child Behavior Checklist (CBCL) and Teachers’ Report Form (TRF) from the Achenbach System of Empirically Based Assessment and the Aberrant Behavior Checklist (ABC). Results: Overall, the results indicated correlations between the MASK scores and problems recorded by teachers, such as Internalizing problems (i.e., Anxious/Depressed, Withdrawn/Depressed, and Other problems score) according to TRF and Inappropriate speech scores, according to teacher’s ABC scales. Schizotypal traits impact the social, emotional, and behavioral functioning of children with ASD at home and school environments. Conclusions: The assessment of schizotypal traits in children with ASD provides critical information about a child’s functionality and cognitive development, also leading to the identification of potential cognitive-neuropsychological endophenotypes within ASD with characteristics of both Autism and Schizophrenia spectra. Τhe development of a valid assessment tool is required, as well as the design of targeted interventions to prevent the loss of functionality.